Probabilistic Network Values - Surajit Borkotokey; Subhadip Chakrabarti; Robert P. Gilles; Loyimee Gogoi; Rajnish Kumar (Queen's University Belfast, Queen's Management School, 2020)
We consider a class of cooperative network games with transferable utilities in which players interact through a probabilistic network rather than a regular, deterministic network. In this class of wealth-generating situations we consider probabilistic extensions of the Myerson value and the position value. For the subclass of probabilistic network games in multilinear form, we establish characterizations of these values using an appropriate formulation of component balancedness. We show axiomatizations based on extensions of the well-accepted properties of equal bargaining power, balanced contributions, and balanced link contributions
Keywords: C71; D85; C71; D85; 330